Design thinking : theory and practice - Pei, Eujin; Becker, Kurt (CRC Press, 2025)
This book aims to provide readers with an in-depth understanding of design thinking by documenting the personal insights of professionals and practitioners from a wide range of disciplines. Design Thinking: Theory and Practice refers to a series of cognitive, strategic, and practical steps used during the process of designing, and the context of how people reason when they engage with solving problems. The scope of this book focuses on topics such as problem-solving, systems thinking, innovation, and the role of design in product design and services. This book is unique as it brings together "stories" from both academics' and practitioners' perspectives, enabling readers to view design thinking from many different perspectives that can be applied in every-day life situations or for organizations when developing plans and policies. This book would be essential reading for design engineers, industrial designers, and mechanical engineers who have interest in design thinking.
Keywords: Design.; elektronické knihy; electronic books